Recent Developments in CRISPR/Cas9 Genome-Editing Technology Related to Plant Disease Resistance and Abiotic Stress Tolerance - İbrahim Erdoğan; Birsen Cevher-Keskin; Özlem Bilir; Yiguo Hong; Mahmut Tör (Biology, 2023)
The revolutionary CRISPR/Cas9 genome-editing technology has emerged as a powerful tool for plant improvement, offering unprecedented precision and efficiency in making targeted gene modifications. This powerful and practical approach to genome editing offers tremendous opportunities for crop improvement, surpassing the capabilities of conventional breeding techniques. This article provides an overview of recent advancements and challenges associated with the application of CRISPR/Cas9 in plant improvement. The potential of CRISPR/Cas9 in terms of developing crops with enhanced resistance to biotic and abiotic stresses is highlighted, with examples of genes edited to confer disease resistance, drought tolerance, salt tolerance, and cold tolerance. Here, we also discuss the importance of off-target effects and the efforts made to mitigate them, including the use of shorter single-guide RNAs and dual Cas9 nickases. Furthermore, alternative delivery methods, such as protein- and RNA-based approaches, are explored, and they could potentially avoid the integration of foreign DNA into the plant genome, thus alleviating concerns related to genetically modified organisms (GMOs). We emphasize the significance of CRISPR/Cas9 in accelerating crop breeding processes, reducing editing time and costs, and enabling the introduction of desired traits at the nucleotide level. As the field of genome editing continues to evolve, it is anticipated that CRISPR/Cas9 will remain a prominent tool for crop improvement, disease resistance, and adaptation to challenging environmental conditions.